A TRANSITIVITY ANALYSIS OF MALE AND FEMALE STUDENTS’ FINAL DRAFT OF CRITICAL RESPONSES PARAGRAPH TO LITERATURE - Nia Siti Hadiyati; Iskhak Said; Bambang Ruby Sugiarto (JALL (Journal of Applied Linguistics and Literacy), 2018)
This study aims at investigating the realization of transitivity particularly process, participant and circumstance types realized in male and female students’ final draft of critical response paragraph to literature. A descriptive qualitative method was employed in analyzing and interpreting the whole data. Furthermore, eight students’ final draft of critical response paragraph to literature which were categorized into male and female students’ critical response paragraph. The findings showed that (1) most of the male and female students were able to realize the transitivity in which the transitivity was realized through the clauses that construct meaning of every single text. (2) Most dominant process realized in eight texts were material process, while actor and goal became the most dominant participants realized and circumstance of location became the most dominant circumstance realized in every single text. However, male students were tend to use the material process in their texts. This study concludes that even though the text were categorized into male and female students’ text, most of the text had realized correctly transitivity while both male and female students’ final draft of critical response paragraph to literature, material process dominantly emerged in the text. Finally, this study suggests English teachers and lecturers to refer the transitivity as a method which can be applied to check whether the students had correctly written critical response or not. Keywords: transitivity, critical response, literature